Nanoscale identification and characterization of the shear strength of minerals and organic matter in shale - de Lacerda, D. L. P.; Prioli, R.; Parizek-Silva, Y. M.; Vasquez, G. F. (Frontiers in Earth Science, 2023)
Shales are composed of minerals and organic matter, whose individual properties are essential to determining the rock’s macroscopical deformation and strength. Scanning electron microscopy combined with electron energy dispersive spectroscopy (EDS) has been extensively used to evaluate composition, while peak-force atomic force microscopy (AFM) has been used on the determination of elastic modulus with nanometric resolution. Still, there is a need for tools to conduct an in-depth study of the minerals’ tribomechanical properties. Atomic force microscopy is a tool that can contribute to these studies, as it can simultaneously measure the tribomechanical properties and identify the phases. In this work, we propose using atomic force microscopy and energy dispersive spectroscopy to identify the shale components and to measure the in situ tribomechanical properties from the different phases. Friction images between the atomic force microscopy tip and the surface were acquired as a function of load. Minerals and organic matter were later identified by colocalized energy dispersive spectroscopy mapping. Then, the frictional characteristics of the major shale constituents were obtained by adjusting the Derjaguin-Muller-Toporov model to the selected components. Moreover, the identification of the different phases was performed. The results show that friction at the nanometer scale was observed to be higher for organic matter than for any other shale constituent, while shear strength was observed to be higher for quartz and lower for organic matter. These characteristics were used to differentiate shale constituents. It is shown that a careful comparison of friction can be used to differentiate the sulfite pyrite, tectosilicates (quartz, andesine, and albite), phyllosilicate biotite, and organic matter. The presented methodology gives novel information on friction properties in the nanoscale that are comparable to available centimetric characterization techniques contributing to the understanding of rock strength.